2014
DOI: 10.1186/1472-6882-14-125
|View full text |Cite
|
Sign up to set email alerts
|

Composition and cytotoxic activity of essential oils from Xylopia aethiopica (Dunal) A. Rich, Xylopia parviflora (A. Rich) Benth.) and Monodora myristica (Gaertn) growing in Chad and Cameroon

Abstract: BackgroundCancer has become a global public health problem and the search for new control measures is urgent. Investigation of plant products such as essential oils from Monodora myristica, Xylopia aethiopica and Xylopia parviflora might lead to new anticancer therapy. In this study, we have investigated the antineoplastic activity of essential oils from fruits of these plants growing in Chad and Cameroon.MethodsThe essential oils obtained by hydrodistillation of fruits of Monodora myristica, Xylopia aethiopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 24 publications
5
35
0
Order By: Relevance
“…; Bakarnga‐Via et al. ), yield of plant extraction could differ according to the season of the harvest and the geographical origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Bakarnga‐Via et al. ), yield of plant extraction could differ according to the season of the harvest and the geographical origin.…”
Section: Discussionmentioning
confidence: 99%
“…), cytotoxic (Bakarnga‐Via et al. ) and antimicrobial (Magina et al. ; Sirirat and Kittipot ; Xing et al.…”
Section: Introductionmentioning
confidence: 99%
“…The fruits are reported to have high nutritive values. It is used as spice all over central and western Africa and as a component of herbal medicines for the treatment of several diseases such as skin infections, cough, bronchitis, dysentery, female sterility, fever and cancer [10]. It has been demonstrated that X. aethiopica fruit methanolic extracts exert cytotoxic activity on pancreatic cancer cells Mia PaCa-2, on leukemia cells CCRF-CEM cells and on cervical cancer C-33A cell lines [11].…”
Section: Introductionmentioning
confidence: 98%
“…However, Kusuhara et al (65) reported that mice kept in a setting enriched with α-pinene showed reduction in melanoma sizes, while in vitro treatment of melanoma cells with α-pinene had no inhibitory effect on cell proliferation, suggesting that the in vivo result may not be due to a direct effect of α-pinene. Investigation of β-pinene also revealed its cytotoxic activity against cancer and normal cell lines with a more pronounced effect on neoplastic cells in the majority of cases, showing acceptable chemotherapeutic potency (66,67).…”
Section: Terpenes and Tumormentioning
confidence: 99%